Development trends of full-scale fire testing - Bula, Serhiy; Boiko, Roman (Видавництво Львівської політехніки, 2013)
The given article concerns the analysis of full-scale fire-tests existing in Ukraine and abroad. Development trends in fullscale fire tests are considered in the article.
Keywords: full-scale fire tests; trends